IOT Based Smart Energy Measurement with Automatic Cost Estimation (International Journal of Scientific Research in Science and Technology, 2024)
In this busy world the people are forgot to pay the electricity bill within the due date. So to reduce that problem we had introduced the smart energy meter. It is used to calculate the electric bill automatically and send the bill amount to the consumers with the help of GSM (Global Service Mobile) through SMS. The controller used in this project is 8051 microcontroller this will just act like a mediator for storing the SMS which is communicated between office and the consumers. Magnetic reed switch will ON and OFF the power to the respective consumers automatically by a single control for the person who not yet paid the bill on or before the due date, so we can eliminate the additional man power which is used earlier. We also added the theft control system; this system will identify that which consumer is pilfering the supply from other consumer furtively. Once the robbery connection is identified with the help of that system, then this will be informed to the authorized consumers through SMS.